Dirlo o non dirlo? Discrezione in situazioni imbarazzanti nella cultura italiana e in quella olandese - Schuiringa, Mathilde; Pinto, Manuela (Incontri. Rivista europea di studi italiani, 2017)
To say or not to say? Discretion in embarrassing situations in Italian and Dutch culture How tactful are Italians and the Dutch in embarrassing situations? This comparative study seeks to determine the factors that affect the degree of direction and communicative strategy used by native speakers of Italian and Dutch when involved in a situation that may cause embarrassment. The data were collected by means of a multiple-choice questionnaire and a discourse completion task. The results show that the two groups use the same strategies. However, a qualitative analysis at the lexical level reveals that Italian speech acts also contain discourse markers (lenitives, downtoners, apologies, etc.), which may explain why Italians are perceived as more tactful.